Spatial-Land use planning system data model proposal for edition II of LADM - Yilmaz, Okan; Surmeneli, Hicret Gursoy; Alkan, Mehmet (TAYLOR & FRANCIS LTD, 2023)
Spatial plan decisions guide both the future use of the lands and many activities from protection to construction and permit. Due to its functions, spatial plan decisions play a key role in land administration. Spatial planning information for integrated land administration systems (LASs) should be associated with land registration systems. The Land Administration Domain Model (LADM) standard offers components to enable this structure. Integrating spatial plan data with LASs will provide standardization for plan data and assurance of plan decisions. Although the spatial planning mission differs across various administrative regions, planning activities produce land use decisions, albeit in different ways. The study aims to establish the common points in planning activities and design a joint spatial planning system data model using various countries' spatial planning systems and international standardization studies. The spatial plans in the model that has been proposed are depicted as a system, not merely by the rights, restrictions, and responsibilities (RRRs) that they establish on the land. The results point out that spatial planning systems have some similarities but also some limitations to support conceptual model design. Based on joint data and relationships, the proposed spatial planning system data model can be adapted for different country practices. The study's results are expected to support the LADM second version development studies.
Keywords: Spatial planning; land use; land administration systems; LADM; 3D legal spaces; RRRs; DESIGN; Environmental Sciences & Ecology; Geology; Remote Sensing; Imaging Science & Photographic Technology